Experimental investigation of cooling time for metal 3D-printed liquid cooling plates in battery thermal management - Seat, Mun Hoe (Nanyang Technological University, 2022)
The utilization of an indirect liquid cooling system in electric vehicles serves as a safe and energy-efficient solution for its battery thermal management due to its high heat transfer rates and greater temperature uniformity on the battery surface. However, the aforementioned cooling solution causes additional thermal resistance during the heat transfer process and huge pressure decline of the circulating coolant. To reduce these disadvantages, metal 3D-printed cooling plates with large cooling cavity are designed and manufactured, so that lightweight and thermal uniformity can be accomplished during the cooling process. The liquid cooling plates are designed with a dimension of 50 × 50 × 6 mm and utilizes the Selective Laser Melting (SLM) metal 3D-printing process. With the implementation of metal 3D-printing process, complex cooling structures of 4mm thickness, which were previously not possible to manufacture using traditional means, are produced. A heat flux of 1049.1±44.9 W/m2 is chosen to replicate the high heat flux encountered in battery operations. The experiment concentrates on the cooling duration for initial temperatures ranging from 40.0°C-45.0°C, to target temperatures of 32.5°C and 35.0°C, which sits in the temperature range of Singapore’s tropical climate and the optimized operating temperature range of 15.0°C-35.0°C. To analyze the impact caused by the temperature of the coolant, water temperatures of 15.9°C, 20.1°C, and 24.6°C are used as the inlet temperatures of the system. Results from the experiment have shown that for the pillar fin structured and body centered cubic (BCC) structured liquid cooling plate with an inlet coolant temperature of 15.9°C, the surface temperature reaches below 35.0°C within 31 seconds and 60 seconds respectively, when the initial surface temperature is 40.0°C and with a constant heat flux. In experiments with inlet coolant temperatures of 24.6°C, the cooling time is found to be 170.7 seconds and 270.7 seconds respectively, with initial conditions maintained. Possible future designs and improvements are also discussed.